Lysosomal pH Is Regulated in a Sex Dependent Manner in Immune Cells Expressing CXorf21 - Harris, Valerie M.; Harley, Isaac T. W.; Kurien, Biji T.; Koelsch, Kristi A.; Scofield, Robert Hal (Frontiers in Immunology, 2019)
Background: CXorf21 and SLC15a4 both contain risk alleles for systemic lupus erythematosus (SLE) and Sjögren’s syndrome (pSS). The former escapes X inactivation. Our group predicts specific endolysosomal-dependent immune responses are driven by the protein products of these genes, which form a complex at the endolysosomal surface. Our previous studies have shown that knocking out CXorf21 increases lysosomal pH in female monocytes, and the present study assesses whether the lysosomal pH in 46,XX women, who overexpress CXorf21 in monocytes, B cells and dendritic cells (DCs), differs from 46,XY men. Methods: To determine endolysosome compartment pH we used both LysoSensor™ Yellow/Blue DND-160 and pHrodo® Red AM Intracellular pH Indicator in primary monocyte, B cells, DCs, NK cells, and T cells from healthy men and women volunteers. Results: Compared to male samples, female monocytes, B cells, and DCs had lower endolysosomal pH (female/male pH value: monocytes 4.9/5.6 p<0.0001; DCs 4.9/5.7 p=0.044; B cells 5.0/5.6 p<0.05). Interestingly, T cells and NK cells, which both express low levels of CXorf21, showed no differential pH levels between men and women. Conclusion: We have previously shown that subjects with two or more X-chromosomes have increased CXorf21 expression in specific primary immune cells. Moreover, knockdown of CXorf21 increases lysosomal pH in female monocytes. The present data show that female monocytes, DC, B cells, where CXorf21 is robustly expressed, have lower lysosomal pH compared to the same immune cell populations from males. The lower pH levels observed in specific female immune cells provide a function to these SLE/SS-associated genes and a mechanism for the reported inflated endolysosomal-dependent immune response observed in women compared to men (i.e. TLR7/type I Interferon activity).